Factores socioculturales que influyen en pacientes con resistencia de Mycobacterium tuberculosis en el Hospital Distrital Santa Isabel 2018 - Medina Rodriguez, Laddy Giovana (2020)
Tuberculosis continues to be a global health and public health problem in developing countries (WORLD HEALTH ORGANIZATION, WHO. 2017). The objective of the present work was to determine the resistance factors of Mycobacterium tuberculosis in the Santa District hospital Isabel 2018. The study units were the medical records of patients diagnosed with resistance to Mycobacterium tuberculosis. A sample size was not calculated, since all the members of the population that met the selection criteria were studied. The highest percentage of resistance was found between 15 and 30 years and 51 to 70 years, both with 43%, the highest percentage of 71% resistance to Mycobacterium tuberculosis corresponds to the male sex, and the lowest percentage corresponds to sex. female with 29%, 43% is presented in users with single marital status, the highest percentage 71% were overweight and normal weight 29%, who traders 29% were resistant, most had full secondary 57%, reported a 14% resistance death, the majority with a favorable evolution 29%, its socioeconomic level is low with 57%., The comorbidity that most affects is diabetes with 57% followed by alcoholism with 15%, the 36% were diagnosed resistant and of them the MDR and monoresistant affected in greater quantity with 43%. Concluding that the frequency of TB in the Santa Isabel District Hospital during the year 2018 was 34 cases, with data recorded of 1 ha This is 6 patients monthly. Of the 34 cases of TB, 7 were determined to be resistant, which constitutes a moderate risk of transmission